Prevalence of malnutrition in children under five years’ age in District Tharparkar Sindh, Pakistan - Bhanwario Menghwar; Zulfiqar Ali Laghari; Salma Farrukh Memon; Jamshed Warsi; Shakil Ahmed Shaikh; Nimra Masood Baig (Journal of the Pakistan Medical Association, 2022)
Objective: To investigate the prevalence of malnutrition in children aged <5 years, and find out the risk factors associated with malnutrition in a rural setting. Method: The survey-based cross-sectional study was conducted from October 2017 to March 2018in four Tehsils of district Tharparkar, Sindh, Pakistan, and comprised children of either gender aged <5 years who were randomly selected and assessed for weight and height using the World Health Organisation Anthro-2007 tool to obtain Z-score. Data was analysed using SPPS Version 18. Results: Of the 597 subjects, 299(50.1%) were girls and 298(49.9%) were boys. Overall, 219(36.7%) were aged 12-23 months and 63(10.5%) were aged 48-59 months. Stunting was found in 485(81.1%) subjects, wasting 112(18.2%) and 342(57.3%) were underweight. The causes of malnutrition included age 6-11 months, number of siblings, monthly income <6000 rupees and duration of breast feeding <12 months (p<0.05). Conclusion: Higher prevalence of malnutrition was found in children aged <5 years in district Tharparkar. Key Words: Malnutrition, Stunting, Wasting, Underweight, Tharparkar, Pakistan. Continuous...